2015
DOI: 10.1007/s13594-015-0257-y
|View full text |Cite
|
Sign up to set email alerts
|

Whey starter addition during maturation of evening milk: effects on some characteristics of cheese milk and Parmigiano–Reggiano cheese

Abstract: Cheese milk "maturation" during natural creaming in large flat vat is a critical step in the production of Parmigiano-Reggiano cheese. Thanks to an improved management, during the last years, a generalized reduction of mesophilic microbial counts has occurred, which did not favour an adequate increase in milk acidity during natural creaming. For this reason, some cheesemakers have introduced the practice to add a rate of natural whey starter in active fermentation in the evening milk to favourize its "maturati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 12 publications
4
8
0
Order By: Relevance
“…The values of the chemical and microbiological parameters were in agreement with those reported by Coloretti et al [ 56 ]. On the same type of milk, these authors found 3.58 g/100 mL fat, 2.55 g/100 mL casein, 5.54 log10 somatic cells/m, 4.85 log10 CFU/mL total mesophilic bacteria and 3.30 log 10 CFU/mL mesophilic lactic acid bacteria.…”
Section: Resultssupporting
confidence: 91%
“…The values of the chemical and microbiological parameters were in agreement with those reported by Coloretti et al [ 56 ]. On the same type of milk, these authors found 3.58 g/100 mL fat, 2.55 g/100 mL casein, 5.54 log10 somatic cells/m, 4.85 log10 CFU/mL total mesophilic bacteria and 3.30 log 10 CFU/mL mesophilic lactic acid bacteria.…”
Section: Resultssupporting
confidence: 91%
“…Indeed, mean values for fecal coliform, enterococci and mesophilic bacteria of whole milk are in agreement with those reported in other studies carried out in the Parmigiano Reggiano area [46][47][48].…”
Section: Effect Of the Milking System On Herd Milk Characteristicssupporting
confidence: 91%
“…Furthermore, also among the microbiological parameters, no one showed significant differences between the cheese produced with milk milked with AMS and with TMP, and all parameters of ripened cheese were in agreement with those reported in the literature by Coppola et al [46] and, more recently, by Coloretti et al [48].…”
Section: Effect Of the Milking System On Vat Milk And Cheese Characte...supporting
confidence: 91%
“…In this specific manufacturing process, milk composition and environmental wild microflora are extremely important (Mordenti et al, 2017). Indeed, the microbial population of whey starter is fundamental for the quality and the maturation process of the cheese (Coloretti et al, 2016). Considering its antimicrobial activity, some have suggested that the administration of monensin might potentially impair cheese composition and quality.…”
Section: Introductionmentioning
confidence: 99%